STATISTICAL STUDY OF TRENDS IN THE PRODUCTION OF VEGETABLE AND GRAPE PRODUCTS IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2024)
This article describes the cultivation of fruits and vegetables and grapes in the country and its regions, their economic and statistical analysis.